The plant-based athlete : a game-changing approach to peak performance - Frazier, Matt; Cheeke, Robert; Holtzman, Rachel (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"A captivating and persuasive scientific exploration of the athletic benefits of a plant-based diet, featuring interviews with stars who've made the switch from meat to plants"--